2003
DOI: 10.1021/jo034424y
|View full text |Cite
|
Sign up to set email alerts
|

First Enantioselective Synthesis and Absolute Stereochemistry Assignment of New Monocyclic Sesquiterpenes from Artemisia chamaemelifolia

Abstract: We herein report the first enantioselective synthesis of two new monocyclic sesquiterpenes from Artemisia chamaemelifolia starting from an enantiopure building block. The key feature of the present approach is to allow complete control of all the stereogenic centers present in the natural products and to elucidate their absolute stereochemistry, which to date is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Originally Marco and co‐workers did not establish the C‐9 stereochemistry of the metabolite found in A. chamaemelifolia 18. Recently, however, Uttaro et al have demonstrated the 9 R stereochemistry of the natural product by means of chemical synthesis and X‐ray crystallographic analysis 20. In our epimeric mixture ( 24 ) the NMR signals corresponding to the major component matched those of the natural metabolite,18 whereas the signals of the minor one agreed closely with those of the 9 S isomer 20.…”
Section: Resultsmentioning
confidence: 62%
“…Originally Marco and co‐workers did not establish the C‐9 stereochemistry of the metabolite found in A. chamaemelifolia 18. Recently, however, Uttaro et al have demonstrated the 9 R stereochemistry of the natural product by means of chemical synthesis and X‐ray crystallographic analysis 20. In our epimeric mixture ( 24 ) the NMR signals corresponding to the major component matched those of the natural metabolite,18 whereas the signals of the minor one agreed closely with those of the 9 S isomer 20.…”
Section: Resultsmentioning
confidence: 62%
“…[18] Recently, however, Uttaro et al have demonstrated the 9R stereochemistry of the natural product by means of chemical synthesis and X-ray crystallographic analysis. [20] In our epimeric mixture (24) the NMR signals corresponding to the major component matched those of the natural metabolite, [18] whereas the signals of the minor one agreed closely with those of the 9S isomer.…”
Section: Synthesis Of Terpenoids With Various Carbocyclic Skeletonsmentioning
confidence: 81%
“…In the final step, treatment of (-)- (14) with the salt-free Wittig reagent gave crystalline karahana lactone (-)-(2). Purification by recrystallization improved the optical purity of (-)-(2) (ee>99%).…”
Section: Methodsmentioning
confidence: 99%
“…This ketol was converted into the single trans-2-carbomethoxy-cyclohexanone (13) by the 1,4 addition of lithium dimethylcuprate, followed by the quenching with methylcyanoformate in HMPA [5]. Treatment of (13) with p-TsOH.H 2 O afforded the crystalline keto-lactone (-)- (14) as a single product. The pathway can be regarded as an acid-induced domino reaction [6] in which the subsequent reaction (cyclization by transesterification) is the result of three reactions (deprotection of (13), epimerization and cyclization).…”
Section: Enantioselective Synthesis Of Both Enantiomers Of Karahana Lmentioning
confidence: 99%
See 1 more Smart Citation